SEGMENTASI PENGGUNA E-WALLET DENGAN MENGGUNAKAN METODE DBSCAN (DENSITY BASED SPATIAL CLUSTERING APPLICATION WITH NOISE) DI KOTA MEDAN - Nurjannah Nasution; Fibri Rakhmawati (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to classify digital wallet users in the city of Medan using the DBSCAN method. The research method used in this study is the method of analysis. The sampling technique uses the Quota sampling technique. The instrument for collecting data in this research was a questionnaire distributed online. Respondents from 10 Medan city sub-districts filled out the questionnaire. Next, analysis of all data was carried out using the following steps: data collection stage, data analysis stage using the DBSCAN method, and conclusions. The research results show that: DBSCAN visualization results on clustering of e-wallet users in the city of Medan can cluster based on the type of e-wallet, what media is used to top-up e-wallet, for what purposes e-wallet is used. So that the level of accuracy The DBSCAN method in this case study is appropriate if we want to do clustering to find out how many e-wallet users there are in the city of Medan